Cost-effectiveness analysis of dasatinib versus imatinib in pediatric philadelphia chromosome-positive acute lymphoblastic leukemia patients in China - Wang Cao; Yuncui Yu; Yingpeng Qiu; Lu Liu; Hao Zhang; Liwei Shi; Yue Xiao; Lulu Jia; Ruidong Zhang; Xiaoling Wang (BMC Health Services Research, 2022)
Abstract Background Dasatinib and imatinib are the recommended tyrosine kinase inhibitors (TKIs) for treating pediatric Philadelphia-positive acute lymphoblastic leukemia (Ph + ALL), and the one which has been approved indication in China is imatinib. Recently, clinical demand for Ph + ALL treatment is becoming unmet gradually with the increasing resistance of imatinib. There are some studies reporting the better efficacy and comparative safety of dasatinib compared with imatinib, but no economic comparison has been published. This study aims to supplement economic evidence by comparing the cost-effectiveness between imatinib and dasatinib in treating pediatric patients with Ph+ ALL in China, and to help clinical rational drug use via multi-dimensional value assessment. Methods A decision tree model combined with a 10-year Markov model were established based on the disease progression. The parameters were collected from published literatures and our hospital’s electronic medical records. From the health system perspective, the incremental cost-effectiveness ratio (ICER) between the two treatment groups was calculated through cost-effectiveness analysis and then compared with the willingness-to-pay (WTP) threshold. The set WTP threshold in this study was 1 times per capita gross domestic product (GDP) of China, as recommended by the World Health Organization. Direct medical costs and quality-adjusted life years (QALYs) were calculated and discounted at 5%. The sensitivity analyses were conducted to assess the uncertainty and robustness of the results. Results The total costs were CNY 1,020,995.35 and CNY 1,035,788.50 in imatinib group and dasatinib group during the 10-year simulation, and the total QALYs were 2.59 and 4.84. Compared with the imatinib treatment group, the ICER was around CNY 6,575.78/ QALY, which was less than the set threshold CNY 70,892/ QALY. The sensitive analyses indicated the robustness of the results. Conclusions The cost-effectiveness analysis shows the potential cost-effective advantages of adding dasatinib comparing with adding imatinib for pediatric Ph + ALL patients in China under the set WTP threshold, which indicates that those patients could achieve more QALYs by paying acceptable fee.